The fulfillment of the copenhagen economic criteria of the European Union : A comparative analysis between Türkiye and other candidate countries - Görgeç, Bilgehan (My University, 2024)
İkinci Dünya Savaşı’nda büyük bir tahribata uğrayan Avrupa Devletleri’nin, Schuman Doktrini’ne dayanarak kömür ve çeliği barışın araçları olarak kullanma arzularıyla tohumları atılan Avrupa Birliği, uluslarüstü bir entegrasyon modelini ifade eder. Avrupa Birliği, ilk olarak 1993 yılında yapılan Kopenhag zirvesinde Orta ve Doğu Avrupa genişlemesi için Kopenhag kriterlerini ortaya koymuş, daha sonra bütün aday ülkelerin tamamlaması için bir gereklilik haline getirmiştir. Siyasi, ekonomik ve topluluk mevzuatının benimsenmesi olmak üzere üç ana gruptan oluşan kriterlerden ekonomik kriterin yerine getirilmesi, Topluluğa tam üyeliğin gerçekleşmesi için önem teşkil etmektedir. Ekonomik kriterin tamamlanması, AB adayı statüsünde bulunan ülkelerin ekonomik performansları doğrultusunda farklılık göstermektedir. Bu çalışmada, Türkiye’nin Kopenhag ekonomik kriterlerini tamamlamasındaki performansı, AB adayı ülkelerle karşılaştırmalı olarak incelenecektir. Karşılaştırma esnasında, ülkelerin Ortaklık Anlaşması, İstikrar ve Ortaklık Anlaşması imzalaması veya aday statüsü kazanması akabinde ekonomik faaliyetlerinin iyileşmesine katkısı olup olmadığı; ülke raporları, ekonomik göstergeler ve siyasi konjonktür ışığında 2013-2022 dönem aralığı için analiz edilecektir. Tezin birinci hipotezi, Avrupa Birliği uyum sürecinin etkisiyle aday ülkelerin ekonomilerinin pozitif yönde ilerleme kaydetmesidir. Tezin ikinci hipotezi Türkiye’nin Avrupa Birliği’nin Kopenhag ekonomik kriterlerini tamamlamakta diğer aday ülkelere göre daha iyi bir konumda olduğudur. Hipotezlerin değerlendirilmesi, belirlenen göstergeler üzerinden karşılaştırmalı grafikler kullanılarak yapılacak; bunun yanı sıra, Kruskal-Wallis H testi ve Mann-Whitney U testlerinin uygulanması ve korelasyon analizi de değerlendirme metodolojisine dahil edilecektir.

The European Union is a supranational organization, which was first established as the European Coal and Steel Community (ECSC) on grounds of the Schuman Doctrine with the efforts of the European countries who were badly destroyed during the Second World War and wanted to use coal and steel as tools to provide peace. The European Union firstly introduced the Copenhagen criteria for Central and East European Countries in the Copenhagen Summit in 1993, and then extended the criteria to all applicant countries as a requirement for full membership. There are three groups of criteria as political, economic, and legislative (acceptance and implementation of all EU acquis), and the fulfilment of economic criteria has an important role in the way of full membership to the Union. In this study, Türkiye's performance in fulfilling the Copenhagen economic criteria is examined in comparison with other EU candidate countries. During the comparison, which will be conducted for the years 2013-2022, whether there is a contribution of countries to the improvement of their economic activities after signing an Association Agreement, Stabilization and Association Agreement, or gaining candidate status will be analyzed in the light of country reports, economic indicators, and the political conjuncture. The first hypothesis of the thesis posits that the economies of the European Union candidate countries have experienced a positive momentum due to the process of harmonization with the European Union. The second hypothesis of the thesis suggests that Türkiye is in a better position to fulfill the European Union's Copenhagen economic criteria plays an important role in the path to full membership to the Union. The evaluation of hypotheses is conducted using comparative graphs based on selected indicators; in addition, the Kruskal-Wallis H test and the Mann-Whitney U test are applied, and correlation analysis is also integrated into the assessment methodology.
Avrupa Birliği Kopenhag ekonomik kriterlerinin yerine getirmesi : Türkiye ve diğer aday ülkeler arasında bir değerlendirme
Keywords: AB Aday Ülkeleri European Union; Avrupa Birliği; Avrupa Birliği ülkeleri; Copenhagen Economic Criteria; Dış ekonomik ilişkiler; Economic Integration; Ekonomik Entegrasyon; EU Candidate Countries; European Union countries; Foreign economic relations; Kopenhag Ekonomik Kriterleri; Türkiye